Hoạt động động đất vùng Nam Trung Bộ, Nam Bộ và lân cận - Sơn, Lê Tử; Xuyên, Nguyễn Đình (Vietnam Journal of Earth Sciences, 2009)
The seismic activities in the South of Central part of Vietnam and adjacent regions ...